Why authenticity in corporate and employee volunteering matters for employee engagement: An organisational behaviour perspective - Paull, M.; Whitsed, Craig (Springer, 2018)
This book explores how the interrelated concepts of responsible citizenship, corporate social responsibility (CSR) and sustainability can be interpreted, researched and taught.